Dispersal of Cotesia flavipes in sugarcane field and implications for parasitoid releases - Dinardo-miranda, Leila Luci; Fracasso, Juliano Vilela; Costa, Viviane Pereira Da; Lopes, Diego Olympio Teixeira [UNESP] (Instituto Agronômico de Campinas, 2014)
Diatraea saccharalis Fabr. (Lepidoptera: Crambidae) is a major sugarcane pest in Brazil. The management of infested areas is based on the release of Cotesia flavipes (Cameron) (Hymenoptera: Braconidae), a parasitoid of D. saccharalis larvae, but there are doubts about the effectiveness of C. flavipes, primarily regarding its rate of dispersal in sugarcane fields. Thus, the objective of this study was to evaluate the dispersal of C. flavipes in a sugarcane field and suggest a release method that provides higher parasitoid efficiency. The study was carried out in four areas of approximately 1 ha, in which stalk pieces containing 20 D. saccharalis larvae were distributed in a rectangular grid, and 12,000 C. flavipes adults were released at four points, that were 50 m apart and 25 m from the field border. Three days later, the D. saccharalis larvae were recovered and kept in the laboratory until they reached pupal stage or C. flavipes emergence. Parasitism varied from 13.2% to 42.8%. The random distribution of parasitized larvae was found in one assay. In three areas, the parasitized larvae showed an aggregated distribution, with a range of 15 to 25 m. Since the parasite's success is directly linked to parasitoid dispersion, it would be interesting to move the release points to 30 m from each other because the dispersal may happen in a 15 m radius.

Diatraea saccharalis Fabr. (Lepidoptera: Crambidae) é uma das principais pragas da cana-de-açúcar no Brasil. O manejo de áreas infestadas é baseado na liberação de Cotesia flavipes (Cameron) (Hymenoptera: Braconidae), um parasitoide de larvas de D. saccharalis, mas existem dúvidas a respeito da eficiência de C. flavipes, principalmente em relação à sua capacidade de dispersão em campo. Assim, o objetivo deste estudo foi avaliar a capacidade de dispersão de C. flavipes em canaviais e sugerir um método de liberação que propicie maior eficiência do parasitoide. O estudo foi conduzido em quatro áreas de aproximadamente 1 ha, e, em cada uma, pedaços de colmos contendo 20 larvas de D. saccharalis foram distribuídos em grid retangular e 12 mil adultos de C. flavipes foram liberados em quatro pontos, separados entre si por 50 m e a 25 m das bordaduras do campo. Três dias depois, as larvas de D. saccharalis foram removidas e mantidas em laboratório até se transformarem em pupas ou até a emergência de C. flavipes. O parasitismo variou de 13,2% a 42,8%. As larvas parasitadas se distribuíram ao acaso em uma área e em três áreas a distribuição foi agregada, com alcance de 15 a 25 m. Visto que o sucesso do parasitismo está diretamente ligado à dispersão do parasitoide, sugere-se que os pontos de liberação estejam distantes entre si 30 m, visto que o raio de dispersão pode ser de 15 m.
Dispersão de Cotesia flavipes em canavial e implicações para a liberação do parasitoide
Keywords: Sugarcane borer; Diatraea saccharalis; Biological control; aggregation; Pest management; Broca da cana; Diatraea saccharalis; Controle biológico; agregação; Manejo de pragas